CD40 Ligand-Dependent Activation of Cytotoxic T Lymphocytes by Adeno-Associated Virus Vectors In Vivo: Role of Immature Dendritic Cells - Zhang, Yi (American Society for Microbiology, 2000)
Recombinant adeno-associated virus type 2 (rAAV) is being explored as a vector for gene therapy because of its broad host range, good safety profile, and persistent transgene expression in vivo. However, accumulating evidence indicates that administration of AAV vector may initiate a detectable cellular and humoral immune response to its transduced neo-antigen in vivo. To elucidate the cellular basis of the AAV-mediated immune response, C57BL/6 mouse bone marrow-derived immature and mature dendritic cells (DCs) were infected with AAV encoding β-galactosidase (AAV-lacZ) and adoptively transferred into mice that had received an intramuscular injection of AAV-lacZ 10 days earlier. Unexpectedly, C57BL/6 mice but not CD40 ligand-deficient (CD40L(−/−)) mice adoptively transferred with AAV-lacZ-infected immature DCs developed a β-galactosidase-specific cytotoxic T-lymphocyte (CTL) response that markedly diminished AAV-lacZ-transduced gene expression in muscle fibers. In contrast, adoptive transfer of AAV-lacZ-infected mature DCs failed to elicit a similar CTL response in vivo. Our findings indicate, for the first time, that immature DCs may be able to elicit a CD40L-dependent T-cell immunity to markedly diminish AAV-lacZ transduced gene expression in vivo when a sufficient number of DCs capturing rAAV vector and/or its transduced gene products is recruited.